1983
DOI: 10.1159/000123517
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunocytochemical Localization of Corticotropin Releasing Factor (CRF-41) and Neurohypophysial Peptides in the Brain of Brattleboro and Long-Evans Rats

Abstract: The localization of CRF-41 related peptide was studied in the brain and posterior pituitary of the homozygous rats for the inherited diabetes insipidus (Brattleboro strain, DI) and of the Long-Evans rats (LE) as control. It was compared to the distribution of vasopressin (AVP), oxytocin (OXY) and OXY-neurophysin (N I). In both strains, CRF-41 was identified in two morphologically distinct systems:one was a hypothalamoneurohypophysial system simultaneously containing CRF-41, OXY and N I; the other was a hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…The results indicated that a moderate number of neurons concentrated in a discrete, anterior, part of the magnocellular division of the PVH jointly expressed CRF and oxytocin immunoreactivity (14,15), while very few neurons centered in the parvocellular division of the nucleus stained positively for both CRF and oxytocin or vasopressin (14).…”
mentioning
confidence: 99%
“…The results indicated that a moderate number of neurons concentrated in a discrete, anterior, part of the magnocellular division of the PVH jointly expressed CRF and oxytocin immunoreactivity (14,15), while very few neurons centered in the parvocellular division of the nucleus stained positively for both CRF and oxytocin or vasopressin (14).…”
mentioning
confidence: 99%
“…A corticotropin-releasing factor (CRF Since the purification and determination of the amino acid sequence of CRF (VALE et al, 1981), some immunohistochemical studies on the localization of CRF neurons in the hypothalamus have been accomplished in rats (MERcHENTHALER et al, 1982;ANTONI et al, 1983;BURLET et al, 1983;KAWATA et al, 1983;SWANSON et al, 1983;TRAMU et al, 1983) and some other mammals (KAWATA et al, 1982). In these reports, it has been debated whether or not CRF and arginine-vasopressin (AVP) or CRF and oxytocin (OXT) might exist in the same neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, it has been debated whether or not CRF and arginine-vasopressin (AVP) or CRF and oxytocin (OXT) might exist in the same neurons. BURLET et al (1983), SWANSON et al (1983), andTRAMU et al (1983) argued for the coexistence of CRF and one of these posterior pituitary hormones, while ANTONI et al (1983) andMERCHENTHALER et al (1982) denied it. These findings were based on the results of comparisons between adjacent serial sections stained immunohistochemically with anti-CRF and anti-OXT (or anti-AVP) sera, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that sympathetic noradrenergic axons are sparse in the pars intermedia of the pituitary and are only present in the vicinity of blood vessels (Björklund, 1968), and that the pars intermedia is controlled by stimulatory β-adrenergic input in addition to inhibitory controls (Munemura et al, 1980;Cote et al, 1982). While the receptor for CRF is also observed in the pars intermedia (Grigoriadis and De Souza, 1989), CRF is localized in the axons of the pars nervosa, but not those of the pars intermedia (Burlet et al, 1983).…”
Section: Control Mechanisms Of the Pars Intermedia (Fig 3) (1) Neuromentioning
confidence: 99%